Trends in the nutritional quality and safety of oils/fats subjected to deep fat frying. - Albuquerque, T.G. (2015)
Introduction: The consumption of fried and prefried foods has been linked with an increase in the intake of fats and oils subjected to high temperatures. The oils and fats are usually processed to improve the quality, stability and safety. Despite removing a large amount of impurities from the oil, the processing can often originate the formation of contaminants that can cause additional health hazards to those who consume these foods. Methods: An extensive bibliographic review with respect to sample preparation, chromatographic methods, and contents of trans fatty acids (TFA), 3-monochloropropane-1,2-diol (3-MCPD) and 4-hydroxy-2-trans-nonenal (HNE) in oils/fats subjected to deep fat frying, has been carried out. Results and Discussion: Some of the chemical reactions that are involved in the frying oils degradation are: hydrolysis, oxidation, isomerisation and polymerisation. These chemical reactions can result in the production of free fatty acids, aldehydes, ketones, diglycerides and monoglycerides, and trans isomers. Over the years, several studies have been conducted in many countries to determine the levels of TFA in foods. Refined oils have low TFA levels (1.0 - 1.5%), but the neutralisation, especially in the preparation of fried foods, can make significant contribution to the daily intake of TFA. Foods that contain partially hydrogenated fats contribute about 80% to 90% of the daily intake of TFA. 3-MCPD is a contaminant resulting from food processing that belongs to the group of chloropropanols. Recently, the occurrence of high levels of 3-MCPD (150 - 10000 µg/kg) in edible oils has been reported. HNE is a cytotoxic and mutagenic secondary lipid peroxidation product of linoleic acid and arachidonic acid which formation is enhanced in deep fat frying. Best approaches to guarantee both quality and safety of fats and oils subjected to deep fat frying are discussed and evaluated.